A Self‐Assembled Rhombohedral DNA Crystal Scaffold with Tunable Cavity Sizes and High‐Resolution Structural Detail. Issue 42 (17th August 2020) - Simmons, Chad R.; MacCulloch, Tara; Zhang, Fei; Liu, Yan; Stephanopoulos, Nicholas; Yan, Hao
Abstract: DNA is an ideal molecule for the construction of 3D crystals with tunable properties owing to its high programmability based on canonical Watson–Crick base pairing, with crystal assembly in all three dimensions facilitated by immobile Holliday junctions and sticky end cohesion. Despite the promise of these systems, only a handful of unique crystal scaffolds have been reported. Herein, we describe a new crystal system with a repeating sequence that mediates the assembly of a 3D scaffold via a series of Holliday junctions linked together with complementary sticky ends. By using an optimized junction sequence, we could determine a high‐resolution (2.7 Å) structure containing R3 crystal symmetry, with a slight subsequent improvement (2.6 Å) using a modified sticky‐end sequence. The immobile Holliday junction sequence allowed us to produce crystals that provided unprecedented atomic detail. In addition, we expanded the crystal cavities by 50 % by adding an additional helical turn between junctions, and we solved the structure to 4.5 Å resolution by molecular replacement. Abstract : A rhombohedral DNA crystal was self‐assembled with prescribed symmetry using a unique immobile Holliday junction sequence. The DNA scaffold contained broad solvent channels along the six‐fold axis and an arrangement of packed layers in a solvent‐excluded environment when viewed at a 90° rotation.